STRATEGI PENDEKATAN PARTISIPATIF PERANGKAT DAERAH DAN DESA DALAM PERCEPATAN INOVASI DI KABUPATEN SUMBAWA BARAT: STRATEGI PENDEKATAN PARTISIPATIF PERANGKAT DAERAH DAN DESA DALAM PERCEPATAN INOVASI DI KABUPATEN SUMBAWA BARAT - Firmansyah, Joni; Hasri, Diah Anggeraini; Agus; Dg Iji, Allein Erida; Irfandi (Fakultas Ilmu Komunikasi Universitas Teknologi Sumbawa, 2024)
This study aims to identify the efforts that can be undertaken by regional and village authorities to enhance innovations in West Sumbawa Regency. The research method used is qualitative-descriptive, employing observation, interviews, and literature study as data collection methods. Interviews were conducted with key informants who are knowledgeable about innovation developments in West Sumbawa Regency. The results of this study indicate that West Sumbawa Regency has significant innovation potential. However, existing innovations are still scattered, and efforts are needed to create an innovation ecosystem. By implementing several strategic steps based on good governance, an innovation ecosystem can be created to accelerate the enhancement of innovations. Another finding of this research explains the need for an innovation center that connects all ideas and concepts from innovators in West Sumbawa Regency. This step is considered to facilitate the community in building interconnected innovation networks. Therefore, through efforts such as village potential analysis, one village-one product initiatives, and innovation month, it is expected that the existing innovations in West Sumbawa Regency can be improved. Keywords: Regional innovation, West Sumbawa Regency, Innovation Ecosystem